QOE Analysis for Mobile Network Services using Twitter Opinion Extraction - Santos, Marcelo; Lopes, Renata (INFOCOMP Journal of Computer Science, 2022)
Mobile communication networks have been evolving over time to meet the expectations of consumers who are increasingly accustomed to the facilities offered by the services provided by such networks. Studies on QoE (quality of experience) are presented to analyze the satisfaction of a final consumer about a given product or service. Thus, this research sought new QoE indicators in an automated way for mobile communications operators that operate in Brazil. Thus, an application was created that sought to mine opinions emitted in tweets from the social network Twitter and score them according to the MOS (Mean Opinion Score). In its results it was possible to observe a tendency of the carriers' customers to use Twitter more to complain than to express opinions of satisfaction. The research observed a scarcity of research that uses a methodology analogous to the one employed, so it believes it can contribute to new research proposals that seek automation in the generation of QoE